Challenges for Primary Health Care Production - Camila Tahis dos Santos Silva; Marluce Maria Araújo Assis; Mariana Mercês Mesquita Espíndola; Maria Angela Alves do Nascimento; Adriano Maia dos Santos (Revista de Enfermagem da Universidade Federal de Santa Maria, 2021)
Objective: to understand the organization of the production of health care in Primary Care. Method: qualitative study, carried out with 23 participants of the family health team by means of interview and systematic observation in seven Family Health Units of the central northern region of Bahia, between May and July 2017; data analysis oriented by Gadamerian hermeneutics. Results: the entrance door is selective; service flows are regulated by offering focused on some services, with long waiting and difficulties in scheduling appointments, besides being disjointed and insufficient for continuity of care. A lack of materials and precarious working conditions was observed. The evaluation is invisible, with insufficient actions to corroborate user satisfaction. Conclusion: there is an evident need for improvement in the organization of primary care and composition of primary care as an organizer of integral and resolute practices in the attention network.